Prevalence of Mandibular Impacted Wisdom Tooth in Relation to Age Factor, Pattern and Level of Impaction: An Observational Study - Sundrani, Dr. Shyam; Gokulakrishnan, Dr. S.; Yadav, Dr. Anurag (International Research in Medical and Health Sciences, 2025)
Background: The registration of impacted wisdom teeth is described by Omar LF. The prevalence of impacted wisdom teeth among young people and is considered to be one of the common problems in dentistry. It is believed that the incidence of impaction has been increasing in recent years due to the less functional activity of the Jaws. The incidence of impaction may differ from one race to another due to the fact of genetically inherited factors and due to the type of food and habits which may have a role in the growth of the jaws.1 Material and Method: A total one hundred twenty-four individuals visiting the Department of Oral and Maxillofacial Surgery, Institute of Dental Sciences, Bareilly who fulfilled the study criteria and consented to participate in this study were recruited based on Observational research. Results: In our study out of 124 study subjects, the maximum 77(62.1%) were in the age group of 21-30 years followed by 32(25.8%) in the age group of 31-40 years and 15(12.1%) in the age group of 18-20 years the mean age of study subjects was 25.36 ± 4.56 years. Conclusion: A strong association was found between impacted wisdom teeth and the type of food and habits among the young population.